2011
DOI: 10.1098/rsbl.2011.0645
|View full text |Cite
|
Sign up to set email alerts
|

To fear or to feed: the effects of turbidity on perception of risk by a marine fish

Abstract: Coral reefs are currently experiencing a number of worsening anthropogenic stressors, with nearshore reefs suffering from increasing sedimentation because of growing human populations and development in coastal regions. In habitats where vision and olfaction serve as the primary sources of information, reduced visual input from suspended sediment may lead to significant alterations in prey fish behaviour. Here, we test whether prey compensate for reduced visual information by increasing their antipredator resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 19 publications
6
62
0
Order By: Relevance
“…Our study is one of the first to show effects of development in turbid water on adult fish behavior (also see Gray et al 2012): although most previous studies document either no change (Ranåker et al 2012) or a decrease (Leahy et al 2011;Borner et al 2015) in baseline activity for adult fish Activity before and after the introduction of a predator cue to assay tanks for both treatments. Grey lines connect multiple trials for individuals.…”
Section: Behavior In Turbid Watermentioning
confidence: 73%
See 2 more Smart Citations
“…Our study is one of the first to show effects of development in turbid water on adult fish behavior (also see Gray et al 2012): although most previous studies document either no change (Ranåker et al 2012) or a decrease (Leahy et al 2011;Borner et al 2015) in baseline activity for adult fish Activity before and after the introduction of a predator cue to assay tanks for both treatments. Grey lines connect multiple trials for individuals.…”
Section: Behavior In Turbid Watermentioning
confidence: 73%
“…Furthermore, previous studies have shown that fish placed in turbid water decrease activity (Leahy et al 2011;Borner et al 2015); thus, we predict that guppies reared in clear water and placed in turbid water will show decreases in activity, while fish reared in turbid water may be acclimated to turbid conditions (in part via transcriptional changes in their visual system) such that activity decrease in turbid water will not be observed. Here, we examine the integrated responses of the visual system and behavior to turbidity over a developmental timescale, demonstrating a multi-dimensional phenotypic response to rapid environmental change.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, this relationship is further influenced by environmental factors such as water turbidity and topographic complexity (hereafter referred to as rugosity) (Beukers and Jones 1997;Rilov et al 2007; Leahy et al 2011). These factors may have complex effects on the predator's ability to detect prey and/or the level of risk perceived by the prey.…”
Section: Introductionmentioning
confidence: 99%
“…As reduced sheltering effectively decreases the benefits derived by host corals from mutualistic damselfishes, an indirect link between overfishing and coral health might exist (Garcia-Herrera et al 2017). Predator avoidance behaviours of site-attached fishes may vary in response to the environmental conditions prevailing on a reef, independently of predator abundance, and may be size-dependent (Leahy et al 2011;Helfman and Winkelman 2015). The size-spectrum theory predicts abundant small-bodied predators and few large-bodied ones (Sogard 1997).…”
Section: Introductionmentioning
confidence: 99%